ANALYSIS OF APPLIED LINGUISTICS IN STUDENTS’ SPEAKING AT MAN KOTA PALANGKA RAYA - Ikrimah, Ikrimah; Soraya, Rika; Altalarik, Agel; Zaini, Muhammad; Asi, Natalina (VISION, 2023)
Applied Linguistics is an academic discipline that utilizes knowledge gained from the study of language to address practical issues and challenges in many contexts. Language abilities are of paramount importance in various domains, including but not limited to the realms of education and language assessment. The objective of this research is to find out the applied linguistics in the students' speaking at MAN Kota Palangka Raya. The researchers employed a descriptive qualitative research design for this study. To gather the data, researchers used recording techniques which were instrumental in capturing videos of the students issuing and accepting invitations. Based on the findings, there were some linguistics features which had been found that applied by the students. They were sound, form, meaning, and construction. It means, the students still find it hard to speak English correctly. To improve, they need to concentrate on the language's rules which involve properly pronouncing words and using appropriate word order and grammar. By focusing on these aspects and applying them consistently, they can speak English much better and communicate their ideas, feelings, and intentions more effectively.